Foliar spray with rutin improves cadmium remediation efficiency excellently by enhancing antioxidation and phytochelatin detoxification of Amaranthus hypochondriacus. Issue 10 (24th August 2022) - Yang, Li; Kang, Yuchen; Liu, Jiaxin; Li, Na; Sun, Hui; Ao, Tianqi; Chen, Wenqing
Abstract: Rutin is a flavonoid with strong antioxidative effects on plant metabolism that facilitates resistance to environmental stress. The effect of foliar rutin on cadmium (Cd) uptake in Amaranthus hypochondriacus (K472) was studied. The results showed that a foliar spray of rutin alleviated Cd toxicity, promoted plant growth, improved Cd transfer to and storage in aerial plant parts and Cd accumulation with positive effects over time. A rutin concentration of 1.5 mg/mL showed the strongest promotion effect: the biomass and Cd content were increased at 13 days by 68.62% and 405.54% compared to 3 days, respectively, whereas a high concentration of rutin (5 mg/mL) inhibited plant growth and hindered Cd absorption. Two stages of Cd detoxification were identified in K472 after appropriate rutin application. First, an antioxidant system including an enzymatic antioxidant (superoxide dismutase [SOD]) and nonenzymatic antioxidants (glutathione [GSH] and flavonoids) was activated to enhance plant stress resistance. Quercetin and phytochelatin (PC) synthesis were then enhanced to perform detoxification synergistically with the antioxidant system to improve stress tolerance and achieve stable Cd detoxification. The results demonstrated that appropriately prolonging the application time of exogenous rutin to K472 is an effective way to improve the Cd remediation efficiency. Novelty statement: The application of exogenous rutin to regulate the growth and Cd absorption of grain amaranth is reported for the first time. A foliar spray of rutin enriches Cd by regulating the metabolism of flavonoids and enhancing antioxidation and phytochelatin detoxification under Cd stress. Properly prolonging the harvest time after rutin treatment can greatly improve the Cd remediation efficiency of soil. The findings of the present study would be helpful for the remediation of Cd-contaminated soils. Graphical Abstract: UF0001 HIGHLIGHTS: Rutin promotes the growth and Cd uptake of Amaranthus hypochondriacus . Extending the treatment time of rutin can improve Cd remediation efficiency. Rutin achieves stress detoxification for Cd by activating antioxidation. The synthesis and transfer of flavonoids and phytochelatin can reduce Cd toxicity.